Atomically crafted spin lattices as model systems for quantum magnetism. (24th June 2015) - Spinelli, A; Rebergen, M P; Otte, and A F
Abstract Low-dimensional quantum magnetism presents a seemingly unlimited source of rich, intriguing physics. Yet, because realistic experimental representations are difficult to come by, the field remains predominantly theoretical. In recent years, artificial spin structures built through manipulation of magnetic atoms in a scanning tunnelling microscope have developed into a promising testing ground for experimental verification of theoretical models. Here, we present an overview of available tools and discuss recent achievements as well as future avenues. Moreover, we show new observations on magnetic switching in a bistable bit that can be used to extrapolate information on the magnetisation of the microscope tip.